Concurrent polyvalent interaction and electrocatalysis to improve lithium-sulfur battery performance - Kumar, Subramani; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2022)
Batteries with improved efficiency are desired. Li-S batteries are attractive due to their high specific capacity and energy density. However, sluggish sulfur redox reaction and polysulfide dissolution are significant challenges in Li-S batteries. In this work, we report graphene with doped layer to electrocatalyze the sluggish sulfur redox reaction. The doped layer comprises heteroatoms such as either N or N and S. The doped layer also comprises cations of Ni. We have chosen a ``doped layer on graphene'' over ``doped graphene'' to avoid defects in the basal plane of graphene. We found the doped layer comprising graphene (DLC-G) to electrocatalyze the polysulfide redox reaction. However, the interaction between the doped layer and polysulfide is still weak, hence the dissolution is not suppressed. To circumvent the polysulfide dissolution, graphene with cationic layer was prepared. We found that cations in the layer electrostatically attract the polysulfides due to the polyvalent interaction. Thus, the dissolution is suppressed. While using this material in the Li-S batteries, the specific capacity, energy density and power density were found to be 1345 mAh g(-1), 782 Wh kg(-1) and 4437 W kg(-1), respectively.
Keywords: electrocatalysis; graphene; lithium-sulfur battery; mechanical exfoliation; polyvalent interaction

Can metal cations electrocatalyze sulfur redox reaction and suppress polysulfide shuttle? - Kumar, Subramani; Swain, Gitanjali; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2023)
In lithium-sulfur (Li-S) batteries, sulfur undergoes various changes. It switches between cyclic structure and linear structure. The charge on the sulfur varies between a neutral state and a negative charge-bearing state. Due to these changes, the sulfur/polysulfide dissolves in the battery electrolyte. Furthermore, the kinetics of the sulfur redox reaction is sluggish. Therefore, a material that can suppress sulfur/polysulfide dissolution and electrocatalyze sulfur redox reaction is needed. We hypothesize that the polysulfide dissolution can be suppressed if the host exhibits polyvalent electrostatic attraction. Polysulfide is a negative charge-bearing molecule; hence the host must comprise multiple positive charges. Nickel cations with other heteroatoms have been explored as a host in Li-S batteries. The heteroatoms impart additional interactions. The easier way to circumvent the effect of heteroatoms is the addition of metal salts. However, metal salts can either exhibit monovalent or divalent attraction with polysulfides. Those interactions are weak and we must have polyvalent interaction. Towards this objective, we have designed and synthesized a material that comprises multiple divalent cations that is also devoid of heteroatoms. The Li-S batteries fabricated using the metal cation immobilized graphene showed a maximum specific capacity of 1022 mAh/g at 0.1 C rate. Among the metal cations, nickel cations showed better performance than cobalt cations. Thus, we demonstrate that metal cations immobilized on Graphene can efficiently electrocatalyze the sluggish sulfur redox reaction and suppress the polysulfide dissolution.
Keywords: electrocatalysis; graphene; lithium-sulfur batteries; metal cations; polysulfides